2016
DOI: 10.1364/oe.24.018163
|View full text |Cite
|
Sign up to set email alerts
|

Micromanipulation of InP lasers with optoelectronic tweezers for integration on a photonic platform

Abstract: Abstract:The integration of light sources on a photonic platform is a key aspect of the fabrication of self-contained photonic circuits with a small footprint that does not have a definitive solution yet. Several approaches are being actively researched for this purpose. In this work we propose optoelectronic tweezers for the manipulation and integration of light sources on a photonic platform and report the positional and angular accuracy of the micromanipulation of standard Fabry-Pérot InP semiconductor lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The resulting nonuniform electric field in the medium interacts with the samples in the liquid medium producing either repulsive (negative DEP) or attractive (positive DEP) force depending on the Clausius–Mossotti (CM) factors of the system . Micro‐objects with similar CM factors (i.e., those with similar material properties and operating conditions) behave similarly in OET systems, and the technique has been applied to manipulate micro‐objects with a wide range of different materials, sizes, and shapes . Figure a,b illustrates the process of patterning 10 µm diameter polystyrene beads in a standard OET device (without micropatterns) to form an “Einstein” cartoon pattern at an AC potential of 7 V p–p at 25 kHz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting nonuniform electric field in the medium interacts with the samples in the liquid medium producing either repulsive (negative DEP) or attractive (positive DEP) force depending on the Clausius–Mossotti (CM) factors of the system . Micro‐objects with similar CM factors (i.e., those with similar material properties and operating conditions) behave similarly in OET systems, and the technique has been applied to manipulate micro‐objects with a wide range of different materials, sizes, and shapes . Figure a,b illustrates the process of patterning 10 µm diameter polystyrene beads in a standard OET device (without micropatterns) to form an “Einstein” cartoon pattern at an AC potential of 7 V p–p at 25 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…[39] Micro-objects with similar CM factors (i.e., those with similar material properties and operating conditions) behave similarly in OET systems, and the technique has been applied to manipulate micro-objects with a wide range of different materials, sizes, and shapes. [4,20,[26][27][28]40,41] Figure 2a,b illustrates the process of patterning 10 µm diameter polystyrene beads in a standard OET device (without micropatterns) to form an "Einstein" cartoon pattern at an AC potential of 7 V p-p at 25 kHz. The polystyrene beads experience negative DEP force and move away from the illuminated regions.…”
Section: Optoelectronic Tweezers and Patterned Optoelectronic Tweezersmentioning
confidence: 99%
“…Compared to conventional optical tweezers, OET traps exert a much stronger manipulation force for a given intensity of light, and in addition OET is well suited for massively parallel manipulation [1,6,7]. To date, there has been demonstration of OET manipulation of many nano-and micro-scale objects, ranging from semiconductor nanowires and carbon nanotubes [8,9], to cells and particles on the order of tens of microns [10][11][12][13][14][15], to photonic/electronic devices with sizes greater than 100 microns [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous OET studies have demonstrated the successful assembly of various nanoscale components, such as semiconductor nanowires, 4 metallic nanowires, 4,5 and metallic spherical nanocrystals. 6 However, there is a growing interest in using OETs to manipulate and assemble large photonic and electronic components with scales of one or several hundreds of microns, such as standard semiconductor microlasers 7 and surface-mount-technology (SMT) capacitors. 8 To build up a photonic or an electronic device containing such large components, it is desirable to use metallic objects with scales of several tens of microns to form a conductive link as this cuts down the number of interfaces between conductive components reducing the chances of a poor connection and associated high resistance.…”
mentioning
confidence: 99%
“…8 To solve this problem, a calculation method based on the integration of the Maxwell stress tensor over the surface of the bead was used, which takes the variation of electric field into account and has been proven to be successful for calculating the DEP force of large objects in varied electric field. 7 Shown in Figure 2(e) (solid lines) are the normalized simulation results of the trap profiles and the measured results (data points). The simulation results were found to be an order of magnitude stronger than the measured results showing that the real OET trap differs from this ideal simulated case.…”
mentioning
confidence: 99%